Phylogeography of the marbled crab Pachygrapsus marmoratus (Decapoda, Grapsidae) along part of the African Mediterranean coast reveals genetic homogeneity across the Siculo-Tunisian Strait versus heterogeneity across the Gibraltar Strait. Issue 5 (27th May 2016) - Deli, Temim; Fratini, Sara; Ragionieri, Lapo; Said, Khaled; Chatti, Noureddine; Schubart, Christoph D.
ABSTRACT: We investigate the influence of previously postulated biogeographic barriers in the Mediterranean Sea on the population genetic structure of a highly dispersive and continuously distributed coastal species. In particular, we examine nuclear and mitochondrial genetic variation in the marbled crab, Pachygrapsus marmoratus, across part of the African Mediterranean coast in order to assess the influence of the Siculo-Tunisian Strait on its population genetic structure. Four polymorphic microsatellite loci were genotyped for 110 individuals, collected from eight locations covering parts of the Algerian, Tunisian and Libyan coasts. In addition, mtDNA corresponding to the Cox1 gene was sequenced for 80 samples. The corresponding results show contrasting patterns of genetic differentiation. While mtDNA results revealed a homogeneous haplotype composition in our study area, microsatellite data depicted genetic differentiation among populations, but not associated with any geographic barrier. This pattern, already recorded for this species from different geographic regions, may hint at the involvement of a complex series of abiotic and biotic factors in determining genetic structure. Demographic history reconstruction, inferred from mtDNA data, supports demographic and spatial expansion for the North African metapopulation dating back to the Mid-Pleistocene and following an historical bottleneck. Comparison of these African mitochondrial sequences with new sequences from a Turkish population and previously published sequences revealed a weak but significant separation of Atlantic and Mediterranean populations across the Gibraltar Strait, which was not recorded in previous studies of this grapsid species.